85‐3: In‐Cell Optical Compensation Technology for OLED Demura Application. Issue 1 (25th September 2020) - Qin, Yunke; Ding, Xiaoliang; Li, Yangbing; Wang, Wenjuan; Zhang, Zhen; Zhang, Ping; Zhao, Fangyuan
Abstract : An in‐cell optical compensation (IOC) technology is verified. The whole device presents a sandwich structure, in which bottom‐emission AMOLED and optical sensor were fabricated onto different substrates and jointed together by adhesive. By optimizing cathode layer, a portion of light could pass through the cathode and be detected by sensor.